2019
DOI: 10.3390/nu11122862
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet on the Gut Microbiota: Rethinking Intervention Duration

Abstract: The human gut is inhabited by trillions of microorganisms composing a dynamic ecosystem implicated in health and disease. The composition of the gut microbiota is unique to each individual and tends to remain relatively stable throughout life, yet daily transient fluctuations are observed. Diet is a key modifiable factor influencing the composition of the gut microbiota, indicating the potential for therapeutic dietary strategies to manipulate microbial diversity, composition, and stability. While diet can ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
387
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(404 citation statements)
references
References 116 publications
15
387
1
1
Order By: Relevance
“…Our data, including metabolomic profiling, suggest that the pathology of inflammatory diseases initiated or caused by exposure to environmental pollutants (e.g., dioxin‐like PCBs) is complex and may involve disturbances in the gut microbiota, liver, and vascular tissues (Deng et al., 2019; Petriello et al, 2018). The literature, including our data, also suggest that nutritional intervention can modulate the gut microbiota (Leeming et al, 2019; Petriello et al., 2018). This suggests that positive lifestyle changes, such as healthful nutrition, can have a disease‐reducing impact already at the level of the gut microbiota.…”
supporting
confidence: 76%
“…Our data, including metabolomic profiling, suggest that the pathology of inflammatory diseases initiated or caused by exposure to environmental pollutants (e.g., dioxin‐like PCBs) is complex and may involve disturbances in the gut microbiota, liver, and vascular tissues (Deng et al., 2019; Petriello et al, 2018). The literature, including our data, also suggest that nutritional intervention can modulate the gut microbiota (Leeming et al, 2019; Petriello et al., 2018). This suggests that positive lifestyle changes, such as healthful nutrition, can have a disease‐reducing impact already at the level of the gut microbiota.…”
supporting
confidence: 76%
“…Several studies found differences in the baseline microbiome of responders versus nonresponders to different diet interventions. Additionally, individuals with differing bacterial gene richness appear to have differing baseline gut microbiota communities that respond distinctively to a given dietary intervention which will influence the diversity of the gut microbe-derived specialized metabolites and circulating metabolites [127][128][129][130][131][132][133][134][135][136].…”
Section: Gut Microbiome/absorptionmentioning
confidence: 99%
“…[37] Increased α-diversity has been associated with foods generally considered as healthy, such as plant consumption or red wine. [38][39][40] Furthermore, commonly used medications such as antibiotics or proton pump inhibitors can decrease gut α-diversity. [41] Regarding the speci c taxonomy of the gut microbiome, the genus Flavonifractor was enriched in βblocker users in both the full and PS-matched cohorts.…”
Section: Discussionmentioning
confidence: 99%